Improving Outcomes of Behavioral Intervention Plans. (September 2017) - Walker, Jennifer D.; Barry, Colleen
According to federal mandates, if a student's behavior impedes their learning or the learning of others, the individualized education program team is required to address this with a functional behavioral assessment (FBA). The intent of the FBA is to determine the function, or reason, of the impeding behavior for the development of a behavioral intervention plan (BIP). The BIP process is a team-based approach that includes goals and interventions that result in positive behavior change. Procedural fidelity, or compliance with the plan, is of utmost importance to success of this process. Unfortunately, such integrity is often lacking, particularly when teachers carry the responsibility of implementing BIPs in the classroom. Therefore, capacity building within the school team is imperative to increase implementation fidelity of BIPs. This article provides practitioners with the tools to organize the monitoring and implementation of BIPs in classroom settings.